2013
DOI: 10.1063/1.4816272
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic biosensor for detection of hemoglobin concentration in human blood: Design considerations

Abstract: Surface plasmon resonance (SPR) sensor for the detection of hemoglobin concentration in human blood is proposed. Previous experimental results describing variation of refractive index of human blood with hemoglobin concentration at different wavelengths are considered for theoretical calculations. The angular interrogation method along with silica substrate and gold layer is considered. The sensor's performance is closely analyzed in terms of well-defined performance parameters: sensitivity, accuracy, resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 23 publications
0
35
1
1
Order By: Relevance
“…(3). The thickness of binding layer has been taken as 5.5 nm which is the size of hemoglobin molecule [33].…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…(3). The thickness of binding layer has been taken as 5.5 nm which is the size of hemoglobin molecule [33].…”
Section: Computational Methodologymentioning
confidence: 99%
“…Sharma has reported that Hb concentration can be analyzed in terms of well-defined performance parameters of SPR sensor [3]. Wang et al experimentally demonstrated that Hb can be detected by SPR principle [4].…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that, at the present time, so many scientific investigations are related to the study of the bio-objects in order to modify the physical and chemical properties of the conjugated organic materials and to predict their use in the general optoelectronics, display and biomedicine [1][2][3][4][5][6]. Our own steps in this direction occupy a special place, because the liquid crystal (LC) structures with the good orienting ability have been successfully applied and different interface conditions have been proposed [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These applications are dependent on the sensitivity of surface plasmon polaritons (SPPs) to the refractive index (RI) of the medium adjacent to the metal surface. 3,4,13,18 Among the various types, grating structure can be compact and robust, which are desirable characteristics for integration into other devices 6 apart from the tunability of the spectral response through geometrical parameters. [10][11][12][19][20][21] Especially, 1D grating can support waveguide, propagating SPPs and/or surface wave modes.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric grating depicts minima in the reflection spectrum corresponding to the SPPs due to the interaction between longitudinal and transverse resonant modes. 10,19,23 The applications of gratings are not limited to the detection of RI, 5,[10][11][12][13]18 but extends to the estimation of analyte height (h) 10,24 where the latter is quite interesting, and the least explored as far as we can ascertain. In the context of detection of h, the spectral shift of surface wave resonance can be quantified, similar to that of RI.…”
Section: Introductionmentioning
confidence: 99%